The effect of comprehensive intervention on family support and the mediating effect between intervention and changes in children’s dietary and physical activity behaviors - Peifen Duan; Chen Li; Songyang Yu; Jianhui Yuan; Xiangxian Feng (PLoS ONE, 2026)
Objective Childhood overweight and obesity have become one of the major global public health problems. Family support plays an important role in the development of children’s healthy behaviors. This study aimed to assess the effect of a comprehensive intervention for childhood obesity on family support and to examine the mediating effect of family support between the intervention and changes in children’s dietary and physical activity behaviors. Methods A cluster-randomized controlled trial was conducted from 2018 to 2019, involving 396 students from eight elementary schools in Changzhi City, China. Data on children’s dietary habits, physical activity, and family support were collected via structured questionnaires. Generalized estimating equation models were used to assess the effect s of the intervention on family support and its mediating effects were examined. Results After one academic year, the intervention group demonstrated a higher level of family support compared to the control group (OR = 2.539, 95% CI: 2.163–5.402), with increases observed from fathers (OR = 1.910, 95% CI: 1.620–4.087), mothers (OR = 3.624, 95% CI: 1.826–4.092), and grandmothers (OR = 1.289, 95% CI: 1.009–1.648). Mediation analysis indicated that changes in family support partially mediated the association between the intervention and improvements in children’s dietary habits and screen time. Conclusions The comprehensive intervention effectively enhanced family support, and changes in family support served as a mediator for the improvements in children’s dietary behaviors. Integrating family based strategies into the comprehensive childhood obesity prevention programs may further enhance intervention efficacy.